Report on the Hungarian Refugee Situation - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. Dept. of Public Information Report on refugees from Hungary in Austria. Fleeing Soviet terror and threat of Soviet Concentration Camps, Hungarians are braving Soviet bullets and freezing weather in their break for freedom. According to the report, airlifts from America are flying them to friendly countries, but there is also a need for additional trains.